2022
DOI: 10.1177/10775463221075401
|View full text |Cite
|
Sign up to set email alerts
|

Research on the resonance frequency splitting mechanism and novel modal characteristics of a rotating tire acoustic cavity

Abstract: Tire acoustic cavity resonance (TACR) noise contributes significantly to interior noise for lower powertrain noise passenger cars and electric cars, which affects the ride comfort obviously. To design sound absorption structures effectively, it is crucial to clarify the evolution mechanism and influence factors of the resonance frequencies and acoustic modal shapes with the running speed. Aiming at these problems, in this paper, a theoretical model of sound wave propagation in a tire acoustic cavity is constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…O'Boy and Walsh [15,16] showed a numerical model of the tire cavity with passive resonators to reduce the TACRN, and the larger the number of resonators was, the better the ability to attenuate the cavity noise over a wider frequency range was. Liu et al [17][18][19] researched the mechanism and characteristics of the frequency split phenomenon and novel modal of TACRN from different aspects, and the obtained function could help to determine the frequency variation range under different conditions, and the theoretical calculation results were verified by the experiment and simulation. The above works showed that the researchers regarded the acoustic wave in the tire cavity as a plane wave, and then analyzed the characteristics of tire acoustic cavity resonance.…”
Section: Introductionmentioning
confidence: 99%
“…O'Boy and Walsh [15,16] showed a numerical model of the tire cavity with passive resonators to reduce the TACRN, and the larger the number of resonators was, the better the ability to attenuate the cavity noise over a wider frequency range was. Liu et al [17][18][19] researched the mechanism and characteristics of the frequency split phenomenon and novel modal of TACRN from different aspects, and the obtained function could help to determine the frequency variation range under different conditions, and the theoretical calculation results were verified by the experiment and simulation. The above works showed that the researchers regarded the acoustic wave in the tire cavity as a plane wave, and then analyzed the characteristics of tire acoustic cavity resonance.…”
Section: Introductionmentioning
confidence: 99%
“…One key observation is that only the first mode of the cavity resonance creates a net force that vertically excites a wheel, while the higher modes do not create a net force. Since Sakata's initial research, several studies have been performed to analyze the influence of tire deflection in the contact patch area by Thompson [5,6], rolling speed by Feng et al [7][8][9][10][11], and the coupling mechanisms between the air cavity and the rim/tire structure by Cao and Bolton [12,13].…”
Section: Introduction 11 Background Of Studymentioning
confidence: 99%
“…Yi et al 18 established a finite element model of tire cavity coupling and studied the effect of road roughness on TACR noise. Liu et al 19,20 studied the effect of rotation on the TACR noise both by the finite element method (FEM) and the superposition theory of traveling waves. They discovered the splitting phenomenon in the natural frequency of TACR noise caused by the tire rotation.…”
Section: Introductionmentioning
confidence: 99%